Pandangan Hindu tentang Pluralisme dalam Kebhinekaan di Indonesia - Ni Luh Ratna Sari; I Komang Suastika Arimbawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Pluralism is a social fact that forms the basis of diversity. But in reality, it does not only give rise to cooperation but also conflict. In the context of religious harmony, theoretical and practical participation from religious elements becomes significant and effective. The shared perception of plurality is an important starting point in determining the next strategic steps. To weave a diversity and produce results without assimilating conflicts, religious dialogue is an ideal way to get to know and understand each other. From there, the pearls of discouraged policies are revealed and become important references for realizing collective expectations. The issue of plurality and harmony is a real challenge for religions, including Hinduism. However, Hindus are very aware, accept, and even highly appreciate plurality as a consequence of life. Every being, be it individual, group identity, religious identity, all have the right to good treatment and respect.